An algorithm to assess calcium bioavailability from foods - Weaver, Connie M.; Wastney, Meryl; Fletcher, Andrew; Lividini, Keith (Elsevier, 2024)
Background The recommended calcium intakes to meet calcium requirements at various ages are based on average population absorption values. Absorption is altered by physiology, the calcium load, and type of food. The calcium intake necessary, therefore, to meet requirements depends upon diet composition, through bioavailability.